Non-Conventional Performance Characterization of Nonel - L. Russell Payne (International Society of Explosives Engineers, 2008)
The use of shock tube in the blasting industry is relatively well characterized and understood within the realms to which it is used. Non-conventional uses of shock tube within the EOD and the Aerospace Industry however has not been as widely researched and published. Characteristics of shock tube such as its reliability, simplicity and its non-electric nature make it ideal for functioning or driving mechanical mechanisms, detonators, and timing devices. Outlined in the text are the performance characteristics of shock tube in an array of atmospheric environments including pressures ranging from ambient to 100,000 ft equivalent atmosphere. In addition the useful exit work energy or impulse of the shock tube for driving these various EOD and Aerospace mechanisms is published as a function of tube lengths and atmospheric pressures. Of particular interest to these devices is the required length of shock tube needed to produce the steady state detonation energies and the accompanying properties of the shock tube at these lengths. Various sources publish an arbitrary run distance for steady state detonation and output some where between 20 cm and 1.0 meter. Statistical and experimental evidence with in the text show these numbers to be low and provides an updated reference for shock tubes usage in nonconventional situations.